Differences in Impulsive Buying Tendencies Based on Gender of College Students Who Use E-Commerce - Nadhira, Defi Syazana; Lusiria, Devi (In Trend : International Journal of Trends in Global Psychological Science and Education, 2025)
Along with this progress, increasingly sophisticated information technology allows humans to fulfill various needs more efficiently, making many activities more practical and effective. One of the significant impacts of the rapid development of technology is the emergence of e-commerce. With e-commerce, it makes things easier for buyers because it provides various features that provide many conveniences. The existence of these features makes consumers tend to do impulsive buying, namely buying goods without careful planning or consideration, without thinking about the use or need for the goods. This research aims to see differences in impulsive buying behavior between male and female students who use e-commerce. This research uses a quantitative approach with the Slovin method to determine a sample consisting of 100 students who use e-commerce. The measuring instrument used is the impulsive buying scale with a total of 30 items. The results of data analysis using IBM SPSS 27 show that the data is normally distributed and homogeneous. Hypothesis testing with the independent sample t-test produces a significance value of 0.000 (p < 0.05), which indicates there is a significant difference in impulsive buying behavior between male and female students. The average impulsive buying score for female students (77.76) is higher than that of male students (58.72), indicating that women are more likely to do impulsive buying.